SUSTAINABLE DEVELOPMENT OF CONSTRUCTION IN THE CONTEXT OF MITIGATING ENVIRONMENTAL POLLUTION - Kramarenko, Arkadij; Manaenkov, Kirill; Melnichuk, Aleksandr; Makushkin, Sergey; Vinichenko, Mikhail (Revista Inclusiones, 2020)
Sustainable development is a general concept regarding the need to find a balance between meeting current human requirements and protecting the interests of future generations, including the need in a safe and healthy environment. The purpose of the research is to form a set of scholarly and methodological propositions in establishing the essence of the sustainable development concept with regard to the construction sector, analyse energy and environmental factors of balanced construction, and identify the methods of reducing carbon emissions. The paper outlines the theoretical definitions of sustainable development, discusses the elements of sustainable development in the construction industry, and shows the essence of environmentally friendly construction. An expert survey has lent insights for setting specific goals of green construction and outlining the types of green construction and the sustainable development potential of the construction industry.